Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Hải Đăng Nguyễn

\(3x-\dfrac{1}{3}-5x=\dfrac{3}{2}-4\)

Hquynh
13 tháng 7 2022 lúc 8:41

\(-2x-\dfrac{1}{3}=\dfrac{3-4.2}{2}\\ -2x-\dfrac{1}{3}=-\dfrac{5}{2}\\ -2x=-\dfrac{5}{2}+\dfrac{1}{3}\\ -2x=\dfrac{-5.3+2}{6}\\ -2x=-\dfrac{13}{6}\\ x=\left(-\dfrac{13}{6}\right):\left(-2\right)\\ x=\dfrac{13}{12}\)

Buddy
13 tháng 7 2022 lúc 8:43

<=>-2x=\(\dfrac{1}{3}+\dfrac{3}{2}-4\)

<=>-2x=\(\dfrac{-13}{6}\)

<=>x=\(\dfrac{13}{12}\)


Các câu hỏi tương tự
Anh Ngoc
Xem chi tiết
Anh Ngoc
Xem chi tiết
Anh Ngoc
Xem chi tiết
Nguyễn Thùy Dương
Xem chi tiết
Vũ Phạm Gia Hân
Xem chi tiết
35. Trần Nguyệt Phương T...
Xem chi tiết
Lan Hương
Xem chi tiết
Phạm Khánh Linh
Xem chi tiết
Ng KimAnhh
Xem chi tiết
Trần Ngọc Ánh
Xem chi tiết